Livelihoods, forests, and conservation in developing countries: an overview - Sunderlin, William D.; Angelsen, A.; Belcher, B.; Burgess, P.; Nasi, Robert; Santoso, L.; Wunder, Sven (2005)
In the growing literature at the interface of rural livelihood improvement and conservation of natural forests, two overarching issues stand out: (1) How and to what extent use of forest resources do and can contribute to poverty alleviation and (2) How and to what extent poverty alleviation and forest conservation are and can be made convergent rather than divergent goals. This article summarizes and evaluates the state-of-the-art knowledge in these domains of thought and identifies priorities for future research.